1982
DOI: 10.1002/ana.410120503
|View full text |Cite
|
Sign up to set email alerts
|

Spinocerebellar degeneration secondary to chronic intestinal malabsorption: A vitamin E deficiency syndrome

Abstract: Two adults are described who developed a progressive neurological disorder more than 20 years after the onset of chronic fat malabsorption. The clinical features included dysarthria, cerebellar ataxia, and prominent proprioceptive loss with depressed or absent tendon reflexes. Serum vitamin E was undetectable in both cases. One patient improved clinically and electrophysiologically after oral therapy with vitamin E. The findings in these patients were similar to those in others recently reported with vitamin E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0
2

Year Published

1983
1983
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(38 citation statements)
references
References 28 publications
2
34
0
2
Order By: Relevance
“…The first reports emphasized the role of vitamin E deficiency in these patients. 33,34 Subsequently, there was a study that reported a patient who had cerebellar syndrome with no evidence of nutritional deficits. 6 During the last decade, there was a general trend to adopt the concept that in many cases, an immunologic mechanism underlies the brain damage, including 1 case in which magnetic resonance imaging studies clearly demonstrated cerebellar (and cerebral) lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The first reports emphasized the role of vitamin E deficiency in these patients. 33,34 Subsequently, there was a study that reported a patient who had cerebellar syndrome with no evidence of nutritional deficits. 6 During the last decade, there was a general trend to adopt the concept that in many cases, an immunologic mechanism underlies the brain damage, including 1 case in which magnetic resonance imaging studies clearly demonstrated cerebellar (and cerebral) lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E deficiency has been documented in patients with cystic fibrosis and multiple ileal resections. 58 Other causes include a familial disorder of vitamin E absorption 78 and abetalipoproteinemia (Bassen-Kornzweig syndrome), an autosomal recessive syndrome with absence of apoprotein B and consequently abnormal vitamin E absorption.…”
mentioning
confidence: 99%
“…Otherwise, vitamin E deficiency is rare in humans and is limited to cases of fat malabsorption and protein energy malnutrition (12). Documented effects of vitamin E deficiency in humans include ataxic neuropathy, pigmentary retinopathy, spinocerebellar syndrome and, in rare cases, skeletal myopathy (13,14), and a number of vitamin E-dependent myopathies have also been documented in animals (15,16). The biochemical explanation for the relationship between vitamin E deficiency and the abovementioned diseases remains obscure, and may involve antioxidant and/or nonantioxidant effects of vitamin E.…”
Section: Introductionmentioning
confidence: 94%